Necrotising fasciitis: case report - Dapunt, Ulrike A.; Klingmann, Alexander; Schmidmaier, Gerhard; Moghaddam-Alvandi, Arash (BMJ case reports, 2013)
A patient in his late 50s who suffered from necrotising fasciitis is described in this case report. The patient first presented at the chest pain unit, where he reported of respiratory distress and showed systemic signs of an infection. Because of progressive skin lesions indicative of necrotising fasciitis on both the lower extremities, the patient was immediately rushed into surgery and was treated at the intensive care unit. Despite receiving immediate treatment, the patient died of this rapidly spreading infectious disease. Because of the fast advance of this disease, we would like to emphasise the importance of early recognition of symptoms.
Gesehen am 09.12.2020